Indirect Environmental Effects on the Gut-Brain Axis in a Wild Mammal - Petrullo, Lauren; Santangeli, Andrea; Wistbacka, Ralf; Husby, Arild; Raulo, Aura (Wiley-Blackwell, 2026)
Inconspicuous interactions between host physiological systems and resident microbial communities may underlie how animals respond to environmental change. For example, immunity and metabolism are regulated in part by the gut microbiota, which can be shaped indirectly by host neuroendocrine function via a 'gut-brain axis'. Yet the sensitivity of this axis in wild vertebrates remains ambiguous. Here, we investigate covariation among environmental quality, glucocorticoids and gut microbiota in a vulnerable population of Siberian flying squirrels (Pteromys volans) inhabiting a region impacted by variable rates of human disturbance. We test competing hypotheses related to direct versus indirect environmental effects (via the gut-brain axis) on adult and juvenile gut microbial communities. Adults housed a richer gut microbiota and had higher hair glucocorticoids that covaried with microbial composition, while juveniles lacked any hormone-microbiome covariation. Environmental quality (patch size and habitat diversity) predicted variation in glucocorticoids but not variation in microbial diversity, suggesting no direct effects on gut microbiota. Instead, structural equation models revealed indirect environmental effects of habitat quality on microbiota via elevations in glucocorticoids in adults. Among juveniles, habitat-induced hormonal responses had no downstream effects on microbial diversity. Together, this provides evidence for age-dependent indirect effects of the environment quality on gut microbial composition in a wild mammal by way of the host neuroendocrine system.